A comparative evaluation of fracture toughness, flexural strength, and acid buffer capability of a bulk-fill alkasite with high-strength glass-ionomer cement: An in vitro study - Battula, MadhuriSai; Kaushik, Mamta; Mehra, Neha; Raj, Vishnu (Dental research journal, 2022)
Although glass-ionomer cement (GIC) has many unique properties and advantages, it still lacks favorable mechanical properties. Cention N is a recent alkasite material with excellent mechanical properties. The purpose of this study was to compare the mechanical properties (fracture toughness [FT] and flexural strength [FS]) and acid buffer capability of an alkasite material to GIC.BackgroundAlthough glass-ionomer cement (GIC) has many unique properties and advantages, it still lacks favorable mechanical properties. Cention N is a recent alkasite material with excellent mechanical properties. The purpose of this study was to compare the mechanical properties (fracture toughness [FT] and flexural strength [FS]) and acid buffer capability of an alkasite material to GIC.In this in vitro study, a total of 60 samples were prepared using Cention N or GIC. Twenty specimens (n = 10) were prepared using beam-shaped Teflon molds for FS, and twenty specimens (n = 10) were prepared with a similar mold with a notch for FT. These were evaluated on a universal testing machine using a three-point bend test. Twenty (n = 10) disk-shaped specimens were prepared for acid buffer capability. The samples were stored in distilled water for a week. This was followed by immersion in lactic acid with a pH of 4 for calculation of the materials acid buffering capacity at 30 and 60 min from exposure using a pH meter. The data obtained were tabulated and subjected to Kolmogorov-Smirnov test and Shapiro-Wilk test to assess the normal distribution and further analyzed using the Student's t-test to assess the level of significance, P < 0.05 was considered statistically significant.Materials and MethodsIn this in vitro study, a total of 60 samples were prepared using Cention N or GIC. Twenty specimens (n = 10) were prepared using beam-shaped Teflon molds for FS, and twenty specimens (n = 10) were prepared with a similar mold with a notch for FT. These were evaluated on a universal testing machine using a three-point bend test. Twenty (n = 10) disk-shaped specimens were prepared for acid buffer capability. The samples were stored in distilled water for a week. This was followed by immersion in lactic acid with a pH of 4 for calculation of the materials acid buffering capacity at 30 and 60 min from exposure using a pH meter. The data obtained were tabulated and subjected to Kolmogorov-Smirnov test and Shapiro-Wilk test to assess the normal distribution and further analyzed using the Student's t-test to assess the level of significance, P < 0.05 was considered statistically significant.The mean FT, FS, and acid buffer capability of Cention N were significantly higher than GIC at P < 0.05.ResultsThe mean FT, FS, and acid buffer capability of Cention N were significantly higher than GIC at P < 0.05.The present study surmised that Cention N exhibited higher FT, FS, and acid buffer capability than GIC.ConclusionThe present study surmised that Cention N exhibited higher FT, FS, and acid buffer capability than GIC.